PERAN KOMUNIKASI DAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN KAPASITAS PETANI PADI - ali alamsyah; Astrid Sri Wahyuni Sumah; Ruhimat Ruhimat; Resi Safitri; Levinda Melati; Miguel Laurensius Lumban Toruan (Universitas Djuanda Bogor, 2026)
The role of communication in Information and Communication Technology (ICT) to improve the capacity of rice farmers is not just a utopia, but can become a reality. The purpose of this study is to examine the role of communication and ICT in improving the capacity of farmers. The research used a quantitative approach with a survey of 114 rice farmers in Ogan Ilir Regency, South Sumatra. The data were analyzed descriptively and inferentially with a correlation test to examine the relationship between ICT variables (social media ownership, digital information sources, and social media support) and farmer capacity and income. The findings show that the adoption rate of basic ICT, particularly social media ownership, has reached 59.6%. However, its use as a source of specific agricultural information is still low (10.5%), with farmers relying more on traditional methods such as discussions in farmer groups (78.1%) and extension workers (58.8%). Correlation analysis proves that there is a significant positive relationship between social media ownership and farmer capacity (r=0.342), between digital information sources and information management skills (r=0.287), and between social media support and improvement (r=0.305). Communication and ICT play a strategic role as an information bridge in improving farmer capacity. The research findings underscore the importance of integrating traditional communication systems (extension workers and farmer groups) with digital platforms to create a more effective support system and accelerate digital transformation in the agricultural sector.